Improving the management of acute coronary syndrome for Aboriginal and non‐Aboriginal patients in a regional hospital. (14th August 2016) - Scalley, Benjamin; Gee, Amanda; Katzenellenbogen, Judith M.; Gilles, Marisa; Jegasothy, Edward; Thompson, Sandra C.
Abstract: Objectives : To determine inequities in clinical adherence to national diagnostic and management guidelines for acute coronary syndrome (ACS) for Aboriginal and non‐Aboriginal ACS patients at a regional hospital. Methods : Covering two study periods (2011–12; 2013–14), records of Aboriginal (n=276) and a random selection of non‐Aboriginal patients (n=333) presenting to the Emergency Department with chest pain were retrospectively reviewed using an audit protocol. Groups were compared using logistic regression, controlling for age, sex and comorbidity. Results : Pathway utilisation improved overall, but risk stratification improved only for non‐Aboriginal patients (OR=3.34, 95%CI 1.88–5.94). Performance of two troponin measurements increased to 88% for both Aboriginal and non‐Aboriginal presentations. Although initially higher for non‐Aboriginal presentations, the likelihood of admission was found to be similar in the repeat audit (75.6% vs 78.6%; p=0.60), reflecting a rise in Aboriginal presentations being admitted (OR=2.30, 95%CI 1.27–4.15). There was no significant difference in proportions transferred, receiving angiograms or for ST Elevation Acute Coronary Syndrome (a severe form of Acute Coronary Syndrome) being thrombolysed. Discharge against medical advice remained higher among Aboriginal presentations (OR=4.22, 95%CI 0.88–20.29). Conclusions and implications : Although there was a general improvement in adherence to the chest pain pathway and a reduction in inequity in the treatment of Aboriginal people, there is continuing need for improvement in adherence to guidelines to optimise the management of ACS in this regional setting.